Somalia : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2020)
This Joint Staff Advisory Note on the Poverty Reduction Strategy Paper discusses that Somalia has made noteworthy progress since 2012 to recover from decades of conflict and state fragmentation. The country has succeeded in rebuilding core state capabilities and organized two democratic national elections in 2012 and 2017. Somalia has now reached the stage where it seeks to fully reengage the international community and is requesting debt relief through the heavily indebted poor countries initiative. The authorities developed the Ninth National Development Plan (NPD9) through a highly consultative, participatory process that ensured full country ownership. The macroeconomic policy objectives of NDP9 are to promote economic growth in an environment of low inflation, sustainable fiscal and current account balances, and healthy foreign exchange reserves. The IMF staff recommends updating framework to incorporate greater support for poverty reduction and additional financing from development partners during the interim period. The IMF staff supports the authorities' commitment to issuing new Somali shilling banknotes, while maintaining de facto dollarization.